Analyzing technological innovation in low and medium-low tech peruvian manufacturing companies - Del Carpio Gallegos, Javier Fernando (2019)
Greater attention should be given to low- and medium-low- tech companies in emerging countries because they contribute a significant share of GDP and employment in their economies. However, innovation practices of these companies have not taken yet the attention of innovation scholars. This article proposes a model to study how absorptive capacity, perceived impact of information sources and expenditure in acquisition of technology are associated with technological innovation practices in Peruvian low- and medium-low-tech manufacturing companies. A sample of 856 manufacturing companies of low- and medium-low- tech was obtained from the first National Survey of Innovation in the Manufacturing Industry carried out in 2012. A SEM model is proposed and has been analyzed using a partial least squares approach. Our study reveals that absorptive capacity is associated to improve technological innovation, that perceived impact of information sources are important for absorptive capacity and that greater importance should be given to the acquisition of technology: machinery, hardware and software.